2008
DOI: 10.1007/s00464-008-9952-6
|View full text |Cite
|
Sign up to set email alerts
|

Does the placement of a FRECA gastrostomy at the time of laparoscopic fundoplication impact on outcome?

Abstract: FP placement at the time of laparoscopic fundoplication does not appear to compromise the outcome of surgery. Neither the size of patient nor the type of wrap is an impediment to its placement and the device can be used shortly after surgery in the majority allowing for an early discharge. Complications are infrequent; however, change to a button device within 2 years of initial placement requires general anaesthetic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…For this reason, most gastrostomy patients in this study received a PEG. According to present paediatric literature, the proportion of children requiring gastrostomy insertion that are NI varies between 41% and 73% (1,2,5,6,8,9,10,11). The large number of NI children in this study (72.4%) requiring gastrostomy is in keeping with other studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For this reason, most gastrostomy patients in this study received a PEG. According to present paediatric literature, the proportion of children requiring gastrostomy insertion that are NI varies between 41% and 73% (1,2,5,6,8,9,10,11). The large number of NI children in this study (72.4%) requiring gastrostomy is in keeping with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report increased complication rates in NI children (2,10,15). Other paediatric studies have observed a higher rate of complications when gastrostomy insertion is combined with fundoplication surgery (8,9,16). In our study, gastrostomy site‐related complications were common.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our series of 20 patients undergoing laparoscopic fundoplication and placement of FREKA® PEG we demonstrated no obvious adverse impact of this procedure when compared to laparoscopic fundoplication alone. The placement, or indeed replacement, of a PEG at the conclusion of an anti-reflux procedure is occasionally mandated, particularly in neuro-developmentally delayed children, as it is safe and does not appear to impact on the efficacy of the fundoplication (Barber et al 2009). …”
Section: Fig 6 Clear Views Obtained During Laparoscopic Assisted Frmentioning
confidence: 99%